(3QSGdI aj GdaQb Hjf GdeYfi GdeUOQj hGdeYfi GdNGU HGdeUOQs - (3eMeO SYjO Hf Ydj Hf YHO GdbGOQ Hf eMjj GdOjf GdMSfj GdLRGFQj , (B1390 (3gčs ((3CMeO eMjj GdOjf GdMSfjs)
(3ChdgG (B:s
(3aEfc SCdJ Yf eYfi bhdge GdeYfi GdeUOQj hGdeYfi GdNGU HGdeUOQ aGYde HGQc Gddg ajce hdce Cf GdeUOQ jSJYed HeYfjjf, GdChd(B: (3GdeYfi GdeUOQj hgh JCKjQ GdaGYd, CYfj JYdb bOQJg HGdeaYhd agh CeQ GYJHGQj fSHj dG hLhO dg aj GdNGQLs
(3BNQgG (B:s
(3hGdcSH WdH GdTjA HeHGTQI CSHGHg GdJj LQJ GdYGOI GdZGdHI HMUhdg YbjgG GNJjGQG gPG eG Cecfj LeYg aGLYd jO GdVfjf Ydjg dCf gPg GdeSCdI ef eVGejf GdEHgGe heRdI GdCbOGes
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdHdGZIs